2019
DOI: 10.1021/jacs.9b08731
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Self-Assembly of Stellated Metallosupramolecules from Multivalent and Complementary Terpyridine-Based Ligands

Abstract: A series of stellated metallosupramolecular architectures have been assembled through threecomponent integrative self-sorting. Building on the complementary ligand pairing, the initial attempts to synthesize the hexagram complex from a combination of X-shaped tetrakis-and V-shaped bis-terpyridine ligands, and Cd II ions, resulted in an unprecedented mixture of stellated octanuclear and dodecanuclear metallocages, which were further isolated by column chromatography. To overcome the unexpected obstacle, the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 71 publications
0
20
0
Order By: Relevance
“…As Scheme 1 shows, tridentate bonding by 2,2':6',2"-tpy is synonymous with binding one metal ion and the ligand is classed as monotopic (having a single metal-binding domain) [4]. The incorporation of two or more 2,2':6',2"-tpy units into a single organic molecule leads to a multitopic ligand [2,[5][6][7] and is a design strategy that has been used to access high nuclearity coordination assemblies [8][9][10]. An alternative approach is to use isomers of terpyridine, such as 3,2':6',3"-tpy (PIN 1 3 ,2 2 :2 6 ,3 3 -terpyridine) and 4,2':6',4"-tpy (PIN 1 4 ,2 2 :2 6 ,3 4 -terpyridine), in which chelation is not possible (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…As Scheme 1 shows, tridentate bonding by 2,2':6',2"-tpy is synonymous with binding one metal ion and the ligand is classed as monotopic (having a single metal-binding domain) [4]. The incorporation of two or more 2,2':6',2"-tpy units into a single organic molecule leads to a multitopic ligand [2,[5][6][7] and is a design strategy that has been used to access high nuclearity coordination assemblies [8][9][10]. An alternative approach is to use isomers of terpyridine, such as 3,2':6',3"-tpy (PIN 1 3 ,2 2 :2 6 ,3 3 -terpyridine) and 4,2':6',4"-tpy (PIN 1 4 ,2 2 :2 6 ,3 4 -terpyridine), in which chelation is not possible (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…A signal at 1529.8827 m/z [the isotope spacing (Δm) = 0.5 amu] was detected, indicating the formation of a doubly charged ion [(−)-1 -2I] 2+ , which was confirmed after matching the experimental and calculated theoretical m/z values (Figure 2, inset). [30][31][32] The peak was further analyzed by means of ESI-TWIM-MS. 33,34 The analysis revealed that [(−)-1 -2I] 2+ had a narrow drift time distribution with the peak maximum at 13.01 ms (Figure 2), indicating the absence of structural isomers or conformers. After confirming the absence of Cu + contamination from the ion source, mass spectrometry unambiguously supported the presence of two Cu + ions in the structure of (−)-1, which were introduced during the CuI-participated reaction between 5 and (−)-4.…”
Section: Synthesis and Structural Determination Of The Quadruple Pt(ii) Stacksmentioning
confidence: 99%
“…After that, the concept of self-sorting was first introduced by Sanders. 25 Very recently, self-sorting systems with fantastic properties have been reported for controlling the final products in reversible reactions, 26 fabricating hierarchical micro-structures, 27,28 separating isomer mixtures, 29 enhancing the proliferation and survival of cells, 30 tissue engineering, 31 and various other fields. 6,[32][33][34][35][36] Based on the self-sorting level, self-sorting assemblies can be usually classified into three types: narcissistic self-sorting, in which each component assembles with its own kind and achieves sorted structures; nonintegrative self-sorting, in which molecules in a mixture assemble with their counter molecules to form sorted structures and each of the assemblies were composed of more than one ingredient; integrative social selfsorting, in which all components in a system combine together in a specific order and all assemblies have a similar or the same structure.…”
Section: Introductionmentioning
confidence: 99%